Non-Endoscopic Parameters for Predicton of Esophageal Varices - Pathak, Rahul; Jha, Roshan; Khadga, Prem; Sharma, Shashi (Journal of Advances in Internal Medicine, 2017)
Introduction: Non invasive assessment of esophageal varices may improve the management and lower the medical and financial burden related to the screening. In this study, Our aim was to validate the prediction of varices using platelet count/spleen diameter ratio and Alanine transaminase/platelet ratio index (APRI). Methods: Fifty patients with newly diagnosed and treatment naive cirrhosis underwent screening endoscopy along with hematological and ultrsonographic studies. Platelet count/spleen diameter ratio and APRI index were assessed and their diagnostic accuracy calculated. Based on previous studies, a cutoff of 909 was applied for platelet count/spleen diameter ratio and cutoff of > 1.3 for APRI. The diagnostic accuracy of both the indices were further evaluated for severity and size of varices. Results: Prevalence of varices was 36% out of which 24% were large varices. Platelet count/spleen size diameter, portal vein diameter and APRI index had significant association for prediction of presence of varices and strongly correlated with size of varices. Platelet count/spleen size diameter of 909 had diagnostic accuracy of 80.5% for prediction of varices with diagnostic accuracy being 95.8 for predicting large varices. APRI index of more than 1.3 had accuracy of 75% for predicting varices and 87.5% for accurately predicting them as large varices. Conclusions: In a resource limited country like ours, where access to specialized and tertiary care hospitals and availability of endoscopy facilities in rural areas is an issue, these non invasive parameters platelet count/spleen diameter and APRI can be taken as a safe and reliable predictor for esophageal varices. Journal of Advances in Internal Medicine 2017;06(02):21-26.